Peningkatan Kualitas Bahan Bakar Padat Biomassa Dengan Proses Densifikasi Dan Torrefaksi - Mochamad Syamsiro (Jurnal Mekanika dan Sistem Termal, 2016)
Biomass is one of the renewable energy resource in Indonesia which has abundant resources potential. Biomass can be converted into energy by using several process method such as thermochemical dan biological processes. Biomass conversion into fuel is available in all three basic forms of matter : solid, liquid and gas. Generally, biomass solid fuel has low mass and energy density. This paper will review the technology to upgrade the quality of the solid fuel by means of densification and torrefaction. Combined densification and torrefaction processes will be an attractive option to produce high quality solid fuel.